The pirate captain's daughter - Bunting, Eve, 1928- (Sleeping Bear Press, 2011)
Upon her mother's death, fifteen-year-old Catherine puts her courage and strength to the test by disguising herself as a boy to join her father, a pirate captain, on a ship whose crew includes men who are trying to steal a treasure from him.